2015
DOI: 10.1021/acs.inorgchem.5b01124
|View full text |Cite
|
Sign up to set email alerts
|

Dioxo–Fluoroalkoxide Tungsten(VI) Complexes for Growth of WOx Thin Films by Aerosol-Assisted Chemical Vapor Deposition

Abstract: The soluble bis(fluoroalkoxide) dioxo tungsten(VI) complexes WO2(OR)2(DME) [1, R = C(CF3)2CH3; 2, R = C(CF3)3] have been synthesized by alkoxide-chloride metathesis and evaluated as precursors for aerosol-assisted chemical vapor deposition (AACVD) of WOx. The (1)H NMR and (19)F NMR spectra of 1 and 2 are consistent with an equilibrium between the dimethoxyethane (DME) complexes 1 and 2 and the solvato complexes WO2(OR)2(CD3CN)2 [1b, R = C(CF3)2CH3; 2b, R = C(CF3)3] in acetonitrile-d3 solution. Studies of the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…Oxygen-bound ligands such as oxo, alkoxide, β-diketonate and β-ketoesterate moieties have found use in single source precursors for the deposition of metal oxides because the preexisting metal oxygen bonding can facilitate conversion of the precursor to the oxide material during deposition [25,[34][35][36]. We have previously demonstrated that oxo alkoxide complexes of the type WO(OR) 4 (R = C(CH 3 ) 2 CF 3 and C(CF 3 ) 2 CH 3 ) and the dioxo derivative WO 2 (OR) 2 L (R = C(CF 3 ) 2 CH 3 , L = DME) are low temperature precursors to WO x films and nanorods, consistent with incorporation of the terminal oxo moieties into the deposits [23,41,42].…”
Section: Precursor Designmentioning
confidence: 74%
See 1 more Smart Citation
“…Oxygen-bound ligands such as oxo, alkoxide, β-diketonate and β-ketoesterate moieties have found use in single source precursors for the deposition of metal oxides because the preexisting metal oxygen bonding can facilitate conversion of the precursor to the oxide material during deposition [25,[34][35][36]. We have previously demonstrated that oxo alkoxide complexes of the type WO(OR) 4 (R = C(CH 3 ) 2 CF 3 and C(CF 3 ) 2 CH 3 ) and the dioxo derivative WO 2 (OR) 2 L (R = C(CF 3 ) 2 CH 3 , L = DME) are low temperature precursors to WO x films and nanorods, consistent with incorporation of the terminal oxo moieties into the deposits [23,41,42].…”
Section: Precursor Designmentioning
confidence: 74%
“…Fluorination of ligands has been shown to increase the volatility of complexes as a result of decreased intermolecular interactions due to the repulsion produced by the fluorine atoms [39,40]. Following this strategy, fluorinated tungsten oxo-alkoxide complexes have been used as WO x AACVD precursors [23,37,41,42]. We now report the synthesis of a series of fluorinated oxo alkoxide complexes WO(OR 3 )L [R = C(CH 3 ) 2 (CF 3 ), C(CH 3 )(CF 3 ) 2 ] that bear the chelating βdiketonate/ketoesterate ligands acetyl acetonate (acac), dipivaloylmethanate (dpm), ethyl acetoacetate (etac) and tert-butyl pivaloyl acetate (tbac) and demonstrate the use of WO(OC(CH 3 ) 2 (CF 3 ))tbac as a precursor for AACVD of WO x films and nanorods.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests a facile pathway for conversion of an alkoxide ligand to a second oxo moiety, a process we have previously noted in the mass spectra of the related oxo alkoxide complexes WO[OC(CH 3 ) 2 CF 3 ] 4 and WO[OC(CF 3 ) 2 CH 3 ] 4 . 33,49 Thermolysis of 10…”
Section: Mass Spectrometrymentioning
confidence: 99%
“…In particular, we envisioned volatile metal–organic complexes bearing intact metal-dioxo functionalities on Mo­(VI) and W­(VI) centers, as sources for the growth of such centers. While vapor-phase deposition of molybdenum and tungsten oxide films has been realized through ALD and chemical vapor deposition (CVD), including examples using volatile oxo-bearing tungsten precursors, , precise control of deposited surface structures has not yet been reported. Previously, Gordon and co-workers reported that amidinato- and acetamidinato- ligand platforms are viable for volatile metal–organic ALD precursors.…”
mentioning
confidence: 99%